Constraints on the spin evolution of young planetary-mass companions. (February 2018) - Bryan, Marta; Benneke, Björn; Knutson, Heather; Batygin, Konstantin; Bowler, Brendan
Abstract Surveys of young star-forming regions have discovered a growing population of planetary-mass (<13M Jup ) companions around young stars1 . There is an ongoing debate as to whether these companions formed like planets (that is, from the circumstellar disk)2, or if they represent the low-mass tail of the star-formation process3 . In this study, we utilize high-resolution spectroscopy to measure rotation rates of three young (2–300 Myr) planetary-mass companions and combine these measurements with published rotation rates for two additional companions4, 5 to provide a picture of the spin distribution of these objects. We compare this distribution to complementary rotation-rate measurements for six brown dwarfs with masses <20M Jup, and show that these distributions are indistinguishable. This suggests that either these two populations formed via the same mechanism, or that processes regulating rotation rates are independent of formation mechanism. We find that rotation rates for both populations are well below their break-up velocities and do not evolve significantly during the first few hundred million years after the end of accretion. This suggests that rotation rates are set during the late stages of accretion, possibly by interactions with a circumplanetary disk. This result has important implications for our understanding of the processes regulating the angular momentum evolution of young planetary-mass objects, and of the physics of gas accretion and disk coupling in the planetary-mass regime. Similar physical processes regulate the angular momentum of gas-giant planets and planetary-mass brown dwarfs. These processes are active mostly during the early phase of planetary evolution as rotation rates do not change after the first 2–300 Myr.